Writing Southern Politics : Contemporary Interpretations and Future Directions. - Steed, Robert P. (The University Press of Kentucky, 2015)
In Writing Southern Politics, leading scholars review the key research and writing on southern politics since World War II. This essential volume covers topical areas such as civil rights, public opinion, political behavior, party development, population movement, governors, legislatures, and women in politics.